Shyness Weakens the Agreeableness-Prosociality Association via Social Self-Efficacy: A Moderated-Mediation Study of Chinese Undergraduates - Sun, Peng; Liu, Zhen; Guo, Qingke; Fan, Junyi (Frontiers in Psychology, 2019)
Using a sample of 1383 undergraduate students (M age = 20.06, N female = 817), this study tested a moderated mediation model in which shyness moderated the association between agreeableness and prosocial behavior, as well as the relation between agreeableness and social self-efficacy. Results showed (when gender, age, and family socio-economic status were controlled) that agreeableness exerted a positive effect on prosocial behavior toward three types of recipients (i.e., family members, friends/acquaintances, strangers), and this effect was mediated by social self-efficacy and moderated by shyness. The relationships between agreeableness and prosocial behavior were more positive under low shyness than that under high shyness condition. In addition, shyness also moderated the first stage of mediation model (i.e., the agreeableness-SSE association), showing that the relation between agreeableness and SSE was more positive under low shyness than that under high shyness condition. Identifying the moderation effect of shyness provides evidence that personality traits may operate in an interactive manner. This may shed new light on why there are inconsistent findings regarding the agreeableness-prosociality association.